Why was astrology criticised in the Middle Ages? Contribution to further research (on the basis of selected treaties of professors of the University of Krakow in the 15th century). - Konarska-Zimnicka, Sylwia (Saeculum Christianum. Pismo Historyczne, 2018)
People have always been interested in distant, mysterious celestial bodies. Astrologers who explored the mysteries of the study of the stars and planets wanted to read them as predictions of future events. Astrological practices were often seen as bordering of magic, which to a large extent influenced the negative perception of this area of study and its supporters, even though astrologers were employed at the kings’ and bishops’ courts, and even at the papal court. The relationship of astrology with occult sciences, which were regarded as sinful and heretical, led to the situation when its proponents were subject to accusations. Particular attention was paid to the fact that the belief in the influence of heavenly bodies on the events taking place in the sublunary world undermines the foundation of the Christian religion, i.e. the dogma of the free will of man. This and other charges constituted a kind of a “catalogue of allegations” that were made against astrology and astrologers throughout the Middle Ages.